A model for distribution of iron impurity during silicon purification by directional solidification. (November 2017) - Wen, Shutao; Tan, Yi; Yuan, Tao; Li, Pingting; Forzan, Michele; Jiang, Dachuan; Dughiero, Fabrizio
Abstract: A theoretical model to determine distribution of iron impurity during silicon purification by directional solidification with fluctuant crystal growth rate is proposed in this paper. The crystal growth rate is fluctuant usually and it has profound effect on the distribution of iron impurity in practical production. The model validation by the distribution of iron impurity during silicon purification by directional solidification in industrial production and the results show that the calculation agrees with existing experimental results. The results also indicate that distribution of iron impurity is directly correlated with the instantaneous value of crystal growth rate. The high fluctuant distribution of iron impurity during silicon purification by directional solidification can be well explained. Many potential applications of the model in practical production are found, such as predicting the distribution of iron impurity with fluctuant crystal growth rate, evaluating the effect degree of production accident, design and optimization of the process parameters and evaluating of maximum yield for raw silicon with different impurity concentration. Silicon purification with low energy consumption is possible based on the research in this paper. Highlights: Distribution of iron impurity is calculated with fluctuant growth rate. High fluctuant distribution of impurity in silicon ingot is explained. Effect degree of production accident can be evaluated by the model. Process parameters can be design and optimization by the model. Maximum yield for different impurity concentration of raw silicon can be evaluated.